A comparative study of laparoscopic assisted vaginal hysterectomy versus total abdominal hysterectomy in benign gynaecological conditions - Sravanthi, Pandala; Shivani, D.; Gunturu, Naga Jyothi (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2021)
Background: Laparoscopic assisted vaginal hysterectomy (LAVH) has become an alternative to Total Abdominal Hysterectomy (TAH) in cases difficult to manage via vaginal route. To compare the TAH and LAVH for benign uterine pathology. Methods: This prospective study conducted with the outcomes of Laparoscopic assisted vaginal hysterectomy with Total abdominal hysterectomy over a period of 2 years in 100 patients who are undergoing hysterectomies for benign uterine pathology. 50 underwent TAH and 50 underwent Laparoscopic Assisted Vaginal hysterectomy. Results: The average duration of surgery in TAH group is 50 minutes and it is 75 minutes in LAVH group (p<0.05). In TAH group, blood loss was more (250-500 ml) in 28% of patients, where as it was <250 ml in 92% of patients in LAVH group. Mean blood loss is 238 ml and 130 ml in TAH and LAVH group (p<0.01). Only 3 (6%) patients in LAVH group required blood transfusion (p>0.05). Recovery and return to work after discharge from hospital was early with LAVH group as early as 2 weeks in 46% of patients. In TAH group, it was late by 4 weeks in 52% of patients and by 6 weeks in 10% of patients. Conclusions: Thus, it can be concluded that LAVH is safe with less blood loss, shorter duration of hospital stay, early recovery to work, and other intra-operative and post-operative complications.